Ogenj je dober sluga, a slab gospodar - Cimperšek, Mitja (Gozdarski vestnik, 2015)
In the initial development period man had used fire for his easier survival and began also to misuse it later. Using the fire, he applied diverse techniques of burning the forest. Through superficial fire he incited a more lush growth in the nature, through slush-and-burn he durably acquired land for living and food production, through cyclic burning he used the land for some time for food production and left it for the nature to take care of forest regeneration. Pyromania on Pohorje reached its peak with %fratarjenje% (a form of slush-and-burn).
Keywords: ogenj; požari; požarjenje; fratarjenje; smreka; bukev; setev; sajenje